Effect of Heat Treatment of Beverage Cans Remelting on Mechanical Properties - Irawan, Doni; ., Nukman; Yani, Irsyadi; Arifin, Amir (International Journal of Membrane Science and Technology, 2023)
This study compared the mechanical properties of the repeated melting of beverage cans. From the effects of the first melting, a chemical composition test was held out, which turned out that the aluminum produced was not explicitly admitted in the aluminum alloy series 2xxx, 3xxx, 4xxx or 6xxx. The semelting process I have increased the element Fe, as well as the addition of elements of Pb and Sn. Part of smelting I and II were annealed and quenched at 400?C with a holding time of 2 hours. The highest tensile strength is held from the first smelting product that has received quenching heat treatment, 9.67 kg/mm2. After remelting, it decreased to 9.07 kg/mm2. Products that have received quenching heat treatment have the most significant impact value, both for the first and second melting products, namely 74.34 BHN and 101.86 BHN. The most significant impact value was obtained from the first smelting product that received annealing heat treatment, which was 0.0388 J/mm2, and after receiving quenching heat treatment, the impact value became 0.0379 J/mm2.